2022
DOI: 10.1002/pon.6052
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of adult cancer patients: A scoping review of sub‐Saharan Africa

Abstract: Objective Psychosocial aspects of adult cancer patients in sub‐Saharan Africa (SSA) have been described in silos of research articles. Integrative analysis of regional evidence is lacking. This review aimed to describe the scope of existing research on mental health problems, identify research gaps and make informed research, policy and practice recommendations. Methods Search was conducted for original peer‐reviewed research articles, irrespective of their quality, on psychosocial aspects of cancer in all SSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…A recent review of psychiatric disorders among cancer patients in sub-Saharan Africa reported a high incidence ( 14 ), with 66.9% presenting with a Diagnostic Statistical Manual-IV disorder ( 15 ). Major depression and anxiety were most prevalent, with diagnostic surveys revealing 16.4%–40.3% of patients were experiencing depression and 8.8%–19.0% experiencing anxiety ( 16 – 19 ).…”
Section: Psychosocial Morbidity In Cancermentioning
confidence: 99%
“…A recent review of psychiatric disorders among cancer patients in sub-Saharan Africa reported a high incidence ( 14 ), with 66.9% presenting with a Diagnostic Statistical Manual-IV disorder ( 15 ). Major depression and anxiety were most prevalent, with diagnostic surveys revealing 16.4%–40.3% of patients were experiencing depression and 8.8%–19.0% experiencing anxiety ( 16 – 19 ).…”
Section: Psychosocial Morbidity In Cancermentioning
confidence: 99%
“…Bizri et al 12 describe challenges in building psycho-oncology services in Lebanon, and Onyeka et al 13 found, with a few exceptions, that huge gaps exist in psychosocial care for patients with cancer in sub-Saharan Africa. Global partnerships can be of value to advance the routine implementation of psychosocial care for patients with cancer and their families.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“…21 Asuzu et al 22 report a pilot psychosocial intervention group in Nigeria that shows potential in supporting breast cancer patients. However, the need for greater attention to interventional research in psychosocial oncology was highlighted by Onyeka et al 13 in a scoping review of the psychosocial aspects of cancer in sub-Saharan Africa. In a similar vein, based on a survey of cancer care providers in Africa, Lounsbury et al 23 provide support for the need for culturally grounded communication research and program design.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
See 2 more Smart Citations